Molecular detection of the human pathogen Rickettsia parkeri strain Atlantic rainforest in Amblyomma ovale ticks in Argentina - Lamattina, Daniela; Tarragona, Evelina Luisa; Nava, Santiago (2018)
Human rickettsioses caused by Rickettsia parkeri strain Atlantic rainforest in Brazil motivated the analysis of Amblyomma ovale ticks in Misiones province, a similar ecological region in northeastern Argentina. During 2010-2017, 393 A. ovale ticks were collected from domestic and wild animals and from vegetation, and 177 were pooled for rickettsial detection by PCR targeting the gltA, ompA and ompB genes. A sample consisting of a pool of two A. ovale adults collected on Nasua nasua was positive for Rickettsia parkeri strain Atlantic rainforest. Since the Atlantic rainforest areas in Brazil share environmental characteristics with Misiones province, the transmission cycle of R. parkeri strain Atlantic rainforest observed in Brazil should be extrapolated to Argentina, where awareness on the possibility of occurrence of rickettsiosis cases caused by this strain should be raised.